(untitled) (Bulletin of criminological association of Ukraine, 2023)
The article emphasizes that since ancient times, medicine has allowed a person to save lives, which, on the one hand, provided high trust and respect for doctors, and on the other hand, placed great responsibility on them. In view of this, certain principles of its implementation, enshrined in legal customs and later in regulatory legal acts, have always acquired special importance in this area of activity. It is emphasized that understanding the historical origins of the legal principles regulating a certain sphere of social relations allows us to take the broadest possible look at those processes that over the centuries have formed national self-consciousness, customs and traditions that have become an integral part of the national mentality. The provisions of the Constitution of Ukraine, the Fundamentals of Ukrainian Legislation on Health Care, resolutions of the Cabinet of Ministers of Ukraine, orders of the Ministry of Health of Ukraine and the Ministry of Internal Affairs of Ukraine, which determine the legal principles of supervision (control) over compliance with standards in the field of health care, are analyzed. It is noted that the basis for the successful implementation of the provisions of the regulatory legal acts studied by us at the organizational and managerial level is formed by administrative and legal norms. Administrative and legal norms form the basis of any management decision in the field of health care at all levels: starting from the head of a department of a separate health care institution and ending with the leadership of the Ministry of Health of Ukraine. Administrative and legal norms direct management influence within clearly defined frameworks, ensuring their legality, planning and gradualness, making possible abuses and offenses impossible.